Cloning and expression of mouse integrin beta p(beta 7): a functional role in Peyer's patch-specific lymphocyte homing. - Hu, M C (1992)
Lymphocytes express integrin receptors, termed lymphocyte Peyer's patch high endothelial venule (HEV) adhesion molecules (LPAMs), that mediate their organ-specific adhesion to specialized HEVs found in mucosal lymphoid organs (Peyer's patches). LPAM-1 consists of a murine integrin alpha 4 noncovalently associated with integrin beta p. Here, we describe the cloning and expression of a mouse cDNA encoding beta p, which is an 806-amino acid transmembrane glycoprotein. The genomic Southern blot analysis indicates that beta p is the murine homologue of human beta 7. The function of alpha 4 beta 7 as a Peyer's patch-specific adhesion molecule was tested directly by expression of the murine beta 7 cDNA in an alpha 4+ beta 7-B-cell line or coexpression of the alpha 4 and beta 7 cDNAs in an alpha 4-beta 7-T-cell line. The transfected cells exhibited a new Peyer's patch-specific adhesive phenotype that could be specifically blocked by monoclonal antibodies against alpha 4 and beta 7. Moreover, an anti-beta 7 monoclonal antibody specifically blocked binding of normal lymphocytes to Peyer's patch HEV but did not inhibit their binding to peripheral lymph node HEVs, indicating that beta 7 is a unique component of the Peyer's patch-specific homing receptor.